2019
DOI: 10.1021/acssuschemeng.9b05045
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Pt@Ir Nanothorns on Carbon Fiber Paper Electrodes for Carboxylic Acid Valorization via Kolbe Electrolysis

Abstract: Valorization of biomass-derived carboxylic acids into drop-in fuels with the input of renewably sourced electricity is promising for a clean and sustainable energy future. Herein, self-supporting core–shell Pt@Ir nanothorns on 3D porous carbon fiber paper anodes have been employed for the electrocatalytic upgrading of carboxylic acids into fuel-range hydrocarbons. The core–shell anode is synthesized by electrodepositing Pt nanothorns on carbon fiber paper followed by galvanic deposition of a thin layer of Ir n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Pt@Ir showed a significantly higher yield for hydrocarbon production than the reference commercial Pt/C catalyst. A self-supporting Pt@Ir NT catalyst with core-shell structure was also synthesized by controllable electrodeposition of Pt NT followed by the galvanic deposition of Ir on its surface in aqueous solutions, directly used as anode for the conversion of octanoate to hydrocarbons, in particular C7 hydrocarbons [248].…”
Section: Two-dimension and Carbonaceous Materialsmentioning
confidence: 99%
“…Pt@Ir showed a significantly higher yield for hydrocarbon production than the reference commercial Pt/C catalyst. A self-supporting Pt@Ir NT catalyst with core-shell structure was also synthesized by controllable electrodeposition of Pt NT followed by the galvanic deposition of Ir on its surface in aqueous solutions, directly used as anode for the conversion of octanoate to hydrocarbons, in particular C7 hydrocarbons [248].…”
Section: Two-dimension and Carbonaceous Materialsmentioning
confidence: 99%
“…Proposed individual steps such as lyocell fiber (LF) preparation, , cellulose carbonization, , and electrochemical deposition on the CF have been studied for a long time; however, the combined fabrication process should consider more exquisite conditions to obtain the high-performance CF/metal NP micro/nanostructure. First, higher cellulose contents in the lyocell-based fiber precursor should be required to trigger higher mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated the method to fabricate CF from high-crystalline LFs; ,, however, a rare study was performed to measure the mechanical strength of the lyocell-based CF, compared to other cellulose-based ones. Although electrochemical deposition of metal NPs was conducted on the CF surface, most studies focused on electrochemical performance and particle formation. …”
Section: Introductionmentioning
confidence: 99%
“…The oxygen revolution reaction (OER, not shown) is the major side reaction that occurs during Kolbe electrolysis at the anode under aqueous conditions, while it is suppressed under anhydrous conditions. 19,24 Pt (in oxidized form under operating conditions) is the most widely studied anode for Kolbe electrolysis, and other noble metal oxides like IrO2, RuO2, and graphene have also been shown to be active for this reaction 16,18,[25][26][27] .…”
mentioning
confidence: 99%